2020
DOI: 10.1186/s12886-020-01726-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of toric intraocular lens implantation based on iTrace wavefront keratometric astigmatism

Abstract: Background Currently, there is no standard technique for determining corneal astigmatism. The iTrace wavefront aberrometry of cornea calculated steep power and axis based on the best Zernike mathematical fit from all topo data within 4 mm circle. It was supposed to be more accurate than iTrace simulated keratometry which was calculated based on only 4 points on the circle of 3 mm. This aim of this study was to evaluate visual outcomes and rotational stability after toric intraocular lens (IOL) implantation usi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Mean absolute lens rotation was less than 1° at both the 1-day and 1-week visits, which was less than previously reported for the TECNIS Toric IOL (1° to 8.38°), 4,9,10,12,[17][18][19] confirming that the squared and frosted haptic design improved rotational stability. These data compared favorably with absolute rotation reported for other toric IOL models, including with the AcrySof Toric IOL (Alcon Laboratories, Inc., Fort Worth, TX, USA) (1.5° to 8.0°), 5,9,18,[20][21][22][23][24] the enVista Toric IOL (Bausch+Lomb, Inc. Rochester, NY, USA) (1.11° to 3.85°), 25,26 and the HOYA XY-1 (HOYA, Tokyo, Japan) (5.43°). 18 The squared and frosted haptic design of the TECNIS Toric II IOL reduces IOL rotation by increasing the static friction between the frosted haptic arms and the capsular bag.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Mean absolute lens rotation was less than 1° at both the 1-day and 1-week visits, which was less than previously reported for the TECNIS Toric IOL (1° to 8.38°), 4,9,10,12,[17][18][19] confirming that the squared and frosted haptic design improved rotational stability. These data compared favorably with absolute rotation reported for other toric IOL models, including with the AcrySof Toric IOL (Alcon Laboratories, Inc., Fort Worth, TX, USA) (1.5° to 8.0°), 5,9,18,[20][21][22][23][24] the enVista Toric IOL (Bausch+Lomb, Inc. Rochester, NY, USA) (1.11° to 3.85°), 25,26 and the HOYA XY-1 (HOYA, Tokyo, Japan) (5.43°). 18 The squared and frosted haptic design of the TECNIS Toric II IOL reduces IOL rotation by increasing the static friction between the frosted haptic arms and the capsular bag.…”
Section: Discussionsupporting
confidence: 64%
“…In comparison to the rotation data presented for the TECNIS Toric II IOL, Zhang et al reported that 31.7% and 5% of subjects implanted with the AcrySof Toric IOL showed >5° and >10° axis misalignment, respectively, at 1 week after surgery. 22 For both the TECNIS Toric II IOL and the Prototype 2 non-toric monofocal IOL, analysis of the mean signed lens orientation showed a small negative change in orientation over time, indicating a clockwise drift (−0.07° with TECNIS Toric II IOL and −0.23° with Prototype 2 non-toric monofocal IOL at the 1-week visit). These findings were opposite to previous reports of counterclockwise rotation 8,9,28 but consistent with two studies reporting clockwise rotation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“… 17 , 18 However, toric IOL alignment could also be determined, either subjectively by optical cut rotation 19 or by image capture and subsequent analysis in graphics editors, 20 , 21 or by the alternative use of aberrometry to separate corneal and lens-induced (respectively internal) astigmatism. 22 …”
Section: Discussionmentioning
confidence: 99%
“…We calculated TCRP for the central 4-mm zone of the pupil. The simK value was derived from the thin-lens formula and was calculated based on four points on a 3-mm circle centered on the corneal vertex 30 SimK evaluations use the anterior surface to represent the total corneal power without knowing posterior corneal information 31 ; this methodology uses the assumption that the anterior–posterior ratio is 0.822 and the corneal thickness is 500 μm 32 . Both TCRP via the Scheimpflug imaging system and simK via ray-tracing aberrometry can be used to calculate total corneal power.…”
Section: Methodsmentioning
confidence: 99%